Jumping plant lice (Hemiptera, Psylloidea) of Bulgaria - an annotated checklist - Pramatarova, Monika; Malenovský, Igor; Gjonov, Ilia (Biodiversity data journal, 2025)
BACKGROUND: Knowledge of the fauna of jumping plant lice or psyllids in Bulgaria is rather scattered. So far, 113 species of psyllids have been recorded from Bulgaria in 51 publications. The aim of this study is to provide an up-to-date checklist of the Psylloidea species from Bulgaria, based on extensive fieldwork by the authors and examination of specimens mainly from the Zoological Collection of Sofia University (BFUS) and the Moravian Museum in Brno (MMBC). In addition, a thorough review of all relevant literature was undertaken to consolidate the existing records. NEW INFORMATION: Twenty-five species of jumping plant lice are recorded here from Bulgaria for the first time. Of these, two species represent new records for Europe: Dyspersakantshavelii (Gegechkori, 1977) and Heterotriozakochiae (Gegechkori, 1975); and three additional species represent new records for the Balkan Peninsula: Arytainillaspartiicola (Šulc, 1912), Craspedoleptaaraneosa Loginova, 1962 and Eryngiofagababugani (Loginova, 1964). A new synonymy is proposed: Colposceniaosmanica Vondráček, 1953 = Colposceniakiritshenkoi Loginova, 1960, syn. nov. A lectotype is designated for C.osmanica to stabilise the nomenclature. Original drawings or photographs of diagnostic characters on male and female terminalia are provided for C.osmanica, D.kantshavelii, Heterotriozaeurotiae (Loginova, 1960) and H.kochiae. Distributional maps summarising all known records from Bulgaria are provided for each species. Where available, photographs of live or mounted specimens and information on host plants are also provided, including new host plant records for 10 species. The previously published records of Aphalarasauteri Burckhardt, 1983, Bactericeraacutipennis (Zetterstedt, 1828), B.reuteri (Šulc, 1913), Dyspersaapicalis (Foerster, 1848), D.viridula (Zetterstedt, 1828), Eryngiofagamesomela (Flor, 1861) and Triozadispar Löw, 1878 from Bulgaria are considered doubtful and these species are deleted from the list of the Bulgarian fauna, which now comprises 130 species from 33 genera and six families of jumping plant lice. This diversity is compared with the known data on Psylloidea in other countries of the Balkan Peninsula and Turkey and the Bulgarian psyllid fauna is discussed from the perspective of biogeography.
Keywords: Balkan Peninsula; new host plant records; new records; taxonomy; Sternorrhyncha; faunistics; biodiversity; new synonymy; psyllids; West Palaearctic; Europe; phytophagous insects